Event chronology analysis of the historical development of tip‐enhanced Raman spectroscopy. (25th November 2020) - Costa, Márcia D.D.; Cançado, Luiz Gustavo; Jorio, Ado
Abstract: In this history review, the development of tip‐enhanced Raman spectroscopy (TERS) is analyzed from the perspective of scientific instrumentation development. TERS is a powerful and label‐free tool for nanocharacterization, still mainly an academic tool, built from the achievements in Raman spectroscopy, surface‐enhanced Raman spectroscopy, scanning probe microscopy, near‐field optics, and plasmonics. We identified three turning points in TERS history so far, based on two approaches to categorize TERS publications. Evidences from our analyses indicate that developments have been made in the scientific understanding of the technique itself, on the technology for its implementation, and on the application of TERS in other fields. Although, in total, more papers have focused on the technological development, application‐oriented works became the most important type of publication in the last years. This development has participation from different actors, but it has been performed mainly by the academic community, alone or in association with national laboratories. Abstract : In this history review, TERS is analyzed from the perspective of scientific instrumentation development. TERS is built from the achievements in Raman spectroscopy, surface‐enhanced Raman spectroscopy, scanning probe microscopy, near‐field optics, and plasmonics. Based on two approaches to categorize TERS publications, we identified three turning points in TERS history so far, indicating that developments were made in scientific understanding and technology development for its implementation, and it is now dominated by application of TERS in other fields.